OP0187 Hydroxychloroquine Blood Levels in Sle: Clarifying Dosing Controversies and Improving Adherence. (9th June 2015) - Durcan, L.J.; Clarke, W.A.; Magder, L.; Petri, M.
Abstract : Background: Hydroxychloroquine (HCQ) is used for systemic lupus erythematosus (SLE) disease activity and its long-term benefits. Its effectiveness is limited by adherence. One way to assess adherence is blood levels of HCQ. There are conflicting data on the relationship between HCQ levels in blood and disease activity. Controversy also exists regarding HCQ dosing; rheumatologists generally recommend dosing based on weight while ophthalmologists advocate the use of height-based "ideal body weight". Objectives: Here we report on the use of hydroxychloroquine blood levels in evaluating adherence, the effect of repeated measurement on blood levels, examine the relationship between blood levels and disease activity and assess whether dosing protocols influence blood levels Methods: SLE disease activity was measured using the SELENA-SLEDAI. HCQ blood levels were measured by liquid chromatography-tandem mass spectrometry, therapeutic range of 500-2000 ng/ml. Patients are prescribed HCQ not to exceed 6.5mg/kg with a maximum daily dose of 400mg. In hemodialysis, 200mg is prescribed after each session. With renal insufficiency, the dose is 200mg daily.When a sub-therapeutic level was detected patients were notified. Patients were divided according to their HCQ level. Levels less than 15ng/ml were considered non-adherent. Levels of 15-500ng/ml were partially adherent, between 500 and 2000ng/ml were therapeutic and greater than 2000ng/ml were supra-therapeutic. Significance of differences was determined based on a Chi Square Test. HCQ groups were compared with respect to mean disease activity levels using ANOVA. A within-person analysis was calculated for each person, their mean activity level during visits when HCQ was greater than 500 ng/ml was compared to disease activity when HCQ was low. The statistical significance of average differences was assessed using a paired t-test. To assess the impact of measurement and counseling on HCQ adherence, we compared the proportion of patients with a HCQ level of 500ng/ml or higher based on how many prior assessments of HCQ the patient had. The statistical significance of change from prior HCQ level was assessed using a Chi Square test for trend. Results: The patient characteristics are outlined in Table 1 . Differences across the groups were observed in terms of age and gender. No differences were seen with renal failure using our dosing regimen but 67% were sub-therapeutic. Blood levels were similar regardless of the height of the patients. Disease activity within therapeutic range and below therapeutic range was not significantly different (SLEDAI 2.37 (SD 2.55) Vs. 2.52 (SD 3.01), p=0.31). At their first measurement 54% were therapeutic and by the third this had increased to 79% (p≤0.0001). Conclusions: HCQ levels are disappointing in not correlating with disease activity. Importantly, we show that weight based dosing is appropriate and that height does not influence blood levels. We may be under-dosing our patients in renal failure. We also show the significant effect of measurement and counseling on adherence levels in SLE. Disclosure of Interest: None declared